Gender Relational Ethics in the Nyambai Tradition: A Living Fiqh al- Munākahāt Perspective on Ta’āruf among the Lampung Indigenous Community - Wahyu Abdul Jafar; Widad Mahdi Jasim; Ahmed Adil Musa Al-Hayani; Edi Mulyono; Supardi Mursalin (Universitas Islam Negeri Jakarta, 2026)
This study examines the Nyambai tradition as a form of cultural ta’āruf among the Saibatin indigenous community of Lampung through the perspective of living fiqh al-munākahāt. Nyambai is a paired traditional dance performed by muli (young women) and mekhanai (young men) that serves as a medium for social interaction, the introduction of potential marriage partners, and an essential element of customary ceremonies, particularly Nayuh wedding rituals. Beyond its aesthetic function, Nyambai embodies social norms and gender ethics that regulate interactions between men and women within the public customary sphere. This qualitative research employs a legal-ethnographic approach, drawing on participant observation, in-depth interviews with customary leaders, performers, and married couples, and documentary analysis of customary texts and fiqh literature. The findings indicate that Nyambai represents a symbolic and regulated form of ta’āruf consistent with key principles of fiqh al-munākahāt, including the protection of honor, proper social conduct, and family formation. The study also highlights ongoing negotiations between customary norms and Islamic legal interpretations. Abstrak Penelitian ini mengkaji tradisi Nyambai sebagai bentuk budaya ta'āruf di kalangan masyarakat adat Saibatin Lampung melalui perspektif hidup fikih munakahat. Nyambai adalah tarian tradisional berpasangan yang dilakukan oleh muli (wanita muda) dan mekhanai (pria muda), yang berfungsi sebagai media interaksi sosial, pengenalan calon pasangan untuk pernikahan, serta elemen penting dalam upacara adat, terutama dalam ritual pernikahan Nayuh. Di luar fungsi estetikanya, Nyambai mewujudkan norma-norma sosial dan etika gender yang mengatur interaksi antara laki-laki dan perempuan di ranah publik adat. Penelitian kualitatif ini menggunakan pendekatan hukum-etnografi, mengacu pada pengamatan peserta, wawancara mendalam dengan pemimpin adat, pemain, dan pasangan suami istri, serta analisis dokumenter teks adat dan literatur fikih. Temuan ini menunjukkan bahwa Nyambai mewakili bentuk simbolis yang diatur oleh ta'āruf, yang konsisten dengan prinsip-prinsip utama fikih munakahat, termasuk perlindungan kehormatan, perilaku sosial yang tepat, dan pembentukan keluarga. Studi ini juga menyoroti negosiasi yang sedang berlangsung antara norma-norma adat dan interpretasi hukum Islam.